60.3k views
1 vote
If -4/3y=-3/4, then y =?

User Caylin
by
5.8k points

2 Answers

3 votes

Answer:

So we have this equation:


(-4)/(3y)=(-3)/(4)

We can multiply both sides by 4 and 3y:


(-4*4*3y)/(3y)=(-3*4*3y)/(4)


-4*4=-3*3y


-16 = -9y

Now we divide both sides by 9:


(-16)/(-9)=y

And we can remove the minus signs:


(16)/(9)=y

If you mean
(-4)/(3)y=(-3)/(4):


-4y*4=-3*3


-16y = -9


y=(9)/(16)

User Arjen Poutsma
by
5.9k points
1 vote

Explanation:

y=-3/4 ÷ -4/3

y=+9/16‌ ‌ ‌ ‌ ‌ ‌ ‌ ‌ ‌ ‌ ‌

User SAK
by
5.5k points